Odnowienie naturalne w rezerwacie przyrody „Czmoń” (Wielkopolska) - Horodecki, Paweł; Jagodziński, Andrzej; Wiczyńska, Katarzyna (Leśne Prace Badawcze, 2014)
The ‘Czmoń’ nature reserve (23.65 ha) was established in 1998 to protect one of the best-retained areas of natural oak-hornbeam forest ( Galio-Carpinetum ) in the center of the Wielkopolska Region. Apart from oak-hornbeam forest, the ash-elm riparian forest ( Querco-Ulmetum ) and alder riparian forest ( Fraxino-Alnetum ) are found in the reserve. These plant communities, both natural and degenerated as a consequence of previous forest management, have created the convenient conditions for assessment the phytocoenoses’ regeneration potential. The aim of this study was to assess the age and species structure of woody species natural regeneration of the whole area of the nature reserve. To achieve that target, during August and September 2012, 142 sample plots were established with the total area 3550 m 2 on which tree and shrub composition and densities were calculated. Woody species regeneration created various diverse communities among individual sub-units, however oak-hornbeam forest species were predominant in the whole regeneration layer. The character of a ‘natural’ forest was retained on a part of the stands. Moreover, regeneration in degenerated parts of the ‘Czmoń’ nature reserve stands is changing according to potential vegetation. Whereas, the establishment of gaps in the Scots pine stands using artificial regeneration was not worthwhile. The natural regeneration structure under the canopy layer of Scots pine stands unambiguously supports the claim that phytocoenoses can regenerate on their own. In spite of the oak regeneration being infrequent, all stands within the ‘Czmoń’ nature reserve retain substantial rejuvenation potential.